Removal of Copper(II) from Aqueous Solution by Cottonseed Carbon - Vedhavalli, S.; Srinivasan, K. (Asian Journal of Chemistry, 2016)
A novel adsorbent, sulphuric acid treated cottonseed carbon after soaking in sodium bicarbonate, was employed for the removal of copper(II) from aqueous solution at concentrations between 1 and 10 mg/L, in batch equilibrium experiments, in order to determine its adsorption properties. The removal of copper by the adsorbent increases with increasing adsorbent dosages. The adsorption mechanism is assumed to be an ion exchange between copper and the sodium present on the surface of cottonseed carbon. The sorption data have been analyzed and fitted to Freundlich adsorption isotherm. The batch sorption kinetics has been tested for first order kinetics reaction models. Results also showed that the intra-particle diffusion of Cu(II) on the carbon was the main-limiting step.